Pendekatan Praktis dalam Penentuan Harga Pokok Produksi UMKM Kue Basah Berbasis Harian - Indah Lia Puspita; Dini Mayaswari; Dwi Adinda; Dela Safitri; Jihan Nayla Mazidah (Journal of Innovative and Creativity (Joecy), 2026)
This community service activity aims to provide assistance to traditional cake MSMEs in determining the cost of production based on daily production activities. The activity was conducted at a traditional cake MSME in Kedondong District, Pesawaran Regency. The methods used included observation, interviews, material presentation, and direct assistance in simple cost of production calculations. The results showed that MSME owners still recorded production costs in a simple manner and determined selling prices based on estimates and market prices. Through the mentoring activity, business owners began to understand the importance of recording production costs, including raw material costs, labor costs, and other supporting costs in determining selling prices. The mentoring activity helped MSME owners understand simple and organized cost of production calculations to support better business management. This activity was limited to one traditional cake MSME and focused only on simple daily production cost calculations. This activity contributes to improving MSME understanding of simple cost accounting and cost of production determination.